ANALISIS FAKTOR RISIKO LABORATORIES KEJADIAN SINDROM SYOK DENGUE PADA PASIEN DEMAM BERDARAH DENGUE - Siprianus Abdu (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
Dengue shock syndrome (DSS) is a failure of blood circulation in DHF patients. It causes loss of plasma in the blood and the impact of increasing of capillary blood permeability. DSS occurs in patients with DHF at degrees III and IV. Manifestations of that, such as rapid and weak pulse, decreased blood pressure, restless patients, cyanosis around the mouth, skin palpable cold and moist, especially on the tip of the nose, fingers and toes. Assessments made for diagnosis are confirmed by the results of a complete blood lab analysis, such as hematocrit, platelet count, leukocytes and hemoglobin. The objectives of the study were to determine the relationship of hemoconcentration, thrombocytopenia, leukocytopenia and decreased hemoglobin with dengue shock syndrome in DHF patients. The type of this research was a quantitative observational analytic with cross-sectional approach or cross section. The population in this study was all hospitalized DHF patients. Sampling technique was nonprobability sampling with consecutive sampling approach. Data were taken from medical records of DHF patients. Data were analyzed bivariate using a Chi Square statistic test. Conclusion revealed that (1) there was no relationship between lycopene with dengue shock syndrome (p = 0.7); (2) there was a relation between hemoglobin decrease with an incidence of dengue shock syndrome (p = 0,000); (3) there was a relationship between hemoconcentration with dengue shock syndrome (p = 0,000); and (4) there was no association between thrombocytopenia with dengue shock syndrome (p = 0.8). So, the decline of hemoglobin and the incidence of hemoconcentration should be the concern of health personnel so that the patient's condition does not continue until the dengue shock syndrome.